The Development of Visual Expertise in ECG Interpretation: An Eye-Tracking Augmented Re Situ Interview Approach. Issue 3 (27th May 2021) - Wu, William; Hall, Andrew K.; Braund, Heather; Bell, Colin R.; Szulewski, Adam
Abstract: Phenomenon: Visual expertise in medicine involves a complex interplay between expert visual behavior patterns and higher-level cognitive processes. Previous studies of visual expertise in medicine have centered around traditionally visually intensive disciplines such as radiology and pathology. However, there is limited study of visual expertise in electrocardiogram (ECG) interpretation, a common clinical task that is associated with high error rates. This qualitatively driven multi-methods study aimed to describe differences in cognitive approaches to ECG interpretation between medical students, emergency medicine (EM) residents, and EM attending physicians. Approach: Ten medical students, 10 EM residents, and 10 EM attending physicians were recruited from one tertiary academic center to participate in this study. Participants interpreted 10 ECGs with a screen-based eye-tracking device, then underwent a subjective re situ interview augmented by playback of the participants' own gaze scan-paths via eye-tracking. Interviews were transcribed verbatim and an emergent thematic analysis was performed across participant groups. Diagnostic speed, accuracy, and heat maps of fixation distribution were collected to supplement the qualitative findings. Findings: Qualitative analysis demonstrated differences among the cohorts in three major themes: dual-process reasoning, ability to prioritize, and clinical implications. These qualitative findings were aligned with differences in visual behavior demonstrated by heat maps of fixation distribution across each ECG. More experienced participants completed ECG interpretation significantly faster and more accurately than less experienced participants. Insights: The cognitive processes related to ECG interpretation differed between novices and more experienced providers in EM. Understanding the differences in cognitive approaches to ECG interpretation between these groups may help inform best practices in teaching this ubiquitous diagnostic skill.